Comparative analysis of MAPK and MKK gene families reveals differential evolutionary patterns in Brachypodium distachyon inbred lines - Jiang, Min (PeerJ, 2021)
BACKGROUND: Mitogen-activated protein kinase (MAPK) cascades are involved with signal transduction in almost every aspect of plant growth and development, as well as biotic and abiotic stress responses. The evolutionary analysis of MAPKs and MKKs in individual or entire plant species has been reported, but the evolutionary patterns in the diverse inbred lines of Brachypodium distachyon are still unclear. RESULTS: We conducted the systematical molecular evolutionary analysis of B. distachyon. A total of 799 MAPKs and 618 MKKs were identified from 53 B. distachyon inbred lines. Remarkably, only three inbred lines had 16 MPKs and most of those inbred lines lacked MPK7-2 members, whereas 12 MKKs existed in almost all B. distachyon inbred lines. Phylogenetic analysis indicated that MAPKs and MKKs were divided into four groups as previously reported, grouping them in the same branch as corresponding members. MPK21-2 was the exception and fell into two groups, which may be due to their exon-intron patterns, especially the untranslated regions (UTRs). We also found that differential evolution patterns of MKK10 paralogues from ancient tandem duplicates may have undergone functional divergence. Expression analyses suggested that MAPKs and MKKs likely played different roles in different genetic contexts within various tissues and with abiotic stresses. CONCLUSION: Our study revealed that UTRs affected the structure and evolution of MPK21-2 genes and the differential evolution of MKK10 paralogues with ancient tandem duplication might have functional divergences. Our findings provide new insights into the functional evolution of genes in closely inbred lines.